2007
DOI: 10.1002/adfm.200700146
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission Electron Microscopy of TiO2 Anatase Films Embedded with Rutile Nanocrystals

Abstract: Photoemission electron microscopy (PEEM) excited by X‐ray and UV sources is used to investigate epitaxial anatase thin films with embedded rutile nanocrystals, a model system for the study of heterocatalysis on mixed‐phase TiO2. Both excitation sources show distinct contrast between the two TiO2 phases; however, the contrast is reversed. Rutile nanocrystals appear darker than the anatase film in X‐ray PEEM images but brighter in UV‐PEEM images. We observe that topography‐induced contrast is dominant in X‐ray P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
128
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(148 citation statements)
references
References 34 publications
19
128
1
Order By: Relevance
“…The enhanced photoelectrochemical activity supposedly is due to the spatial charge separation across the anatase/rutile interfaces as a result of a staggered band alignment. [ 16 ] The researchers have found that TiO 2 /MWCNT(multiwalled carbon nanotube) composites show improved photocatalysis [ 17 , 18 ] , but they do not enhance the photocatalytic activity of TiO 2 to the same extent as the SWCNT because there is much less individual contact between the MWCNT and the TiO 2 surface. Taking advantage of the large surface area, extraordinary electrical conductivity, robust mechanical strength, and thermal stability of SWCNTs, SWCNT/TiO 2 composite materials have been employed in applications that range from solar cell to environmental concerns.…”
Section: Doi: 101002/adma201103030mentioning
confidence: 99%
“…The enhanced photoelectrochemical activity supposedly is due to the spatial charge separation across the anatase/rutile interfaces as a result of a staggered band alignment. [ 16 ] The researchers have found that TiO 2 /MWCNT(multiwalled carbon nanotube) composites show improved photocatalysis [ 17 , 18 ] , but they do not enhance the photocatalytic activity of TiO 2 to the same extent as the SWCNT because there is much less individual contact between the MWCNT and the TiO 2 surface. Taking advantage of the large surface area, extraordinary electrical conductivity, robust mechanical strength, and thermal stability of SWCNTs, SWCNT/TiO 2 composite materials have been employed in applications that range from solar cell to environmental concerns.…”
Section: Doi: 101002/adma201103030mentioning
confidence: 99%
“…Moreover, the work function of noble metals is generally larger than TiO 2 [15][16][17][18][19]. Therefore, the combination of their different work functions forms a contact barrier that also influences the migration and lifetime of the photogenerated carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TixO2 behaves as an acceptor of SPR excited hot electrons from Ag in the Ag/TixO2 hybrid ( Figure 25B). 103 As the work function of Ag is estimated to be smaller than that of TixO2 (4.8 vs 5.0), 103,124,125 AgNPs→TixO2 electron transfer should readily occur upon contact and intensify under laser radiation. This leads to the accumulation of positive charges (holes) in the Ag NPs that can also act as a direct oxidizing agents, subtracting electrons from PATP molecules and driving its oxidation to DMAB ( Figure 25B).…”
Section: Silver-based Hybrid Materialsmentioning
confidence: 99%
“…However, the activity for Ag/TixO2 was lower as compared to Ag/prGO, indicating that the PATP oxidation by the adsorbed O2 pathway (involving transfer of SPR-excited hot electrons) presented a higher contribution relative to the role of holes as oxidizing agents towards the formation of DMAB. 103,[125][126][127][128] In (A), electrons can be transferred from prGO to Ag NPs, increasing the populations of hot electrons that can be transferred to adsorbed O2 producing O2 -and contributing to the PATP oxidation (hot electron pathway). In (B), charge transfer from Ag to TixO2 takes place, and the PATP is oxidized by the SPR-generated holes in Ag NPs (hole pathway).…”
Section: Silver-based Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation